THE STUDY OF TRANSLATION TECHNIQUE ON MANUAL INSTRUCTION OF ELECTRONIC DEVICES - Kirmadi Kirmadi; Erwin Ashari; Shalehoddin Shalehoddin (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2021)
This study was aimed to analyze translation technique on manual instruction of electronic devices at PT. Philips. The objectives of this study are the first to find out the most dominant of the translation techniques used in translation techniques of manual instruction book ‘Philips’ electronic iron. The second is to identify the translation techniques used in in translation techniques of manual instruction book ‘Philips’ electronic iron in case English to Indonesian language. This study applied descriptive qualitative approach in analyzing of the data obtained. The data based on the text of the instruction manual on the Philip electronic devices. The findings of this study showed that there are 120 data consist of 8 words, 55 phrases and 57 sentences on the manual instruction of Philips electronic iron especially translation in English to Bahasa Indonesia. The techniques Calque was mostly applied in translation with 25 frequencies (18.33%), then the second position is Borrowing with 22 frequencies (18.33%), then third is Establish Equivalent with 16 frequencies (13.33%), the fourth is Particularization with 13 frequencies (10.83%), the next is Literal with 10 frequencies (8.33%), the next is Adaptation with 9 frequencies (7.50%), then the next is Discursive Creation with 9 frequencies (7.50%), Amplification with 7 frequencies (5.83%), Transposition with 4 frequencies (3.33%), Generalization with 4 frequencies (3.33%) and the last is Reduction with 1 frequency (0.83%).. This study could be concluded that the translator tended to translate foreign words or phrases more lexically and structurally rather than other techniques